The Importance of Clotho Proteinin the Development of Chronic Kidney Disease in the Context of Chronic Heart Failure - Djuraeva Nozima Orifovna (American Journal of Biomedicine and Pharmacy, 2025)
The review article presents current research data on the importance of the Clotho proteinin the pathogenesis of chronic kidney disease in the context of chronic heart failure. The relationship of the Clotho protein with fibroblast growth factor–23 and its antioxidant properties is presented. It has been describedthat the α–clotho protein reduces the development of endothelial dysfunction and atherosclerosis by reducing oxidative stress and inflammation.